Productivity of Zakat Management Organizations (OPZ) in Indonesia Based on Malmquist Productivity Index " - Ririn Riani (International Journal of Zakat, 2022)
This paper discusses the efficiency and productivity of zakat management organizations in Indonesia based on the Malmquist Productivity Index. This type of research is quantitative research. The data used is a time series and cross-section from 2016-2019 using the Malmquist Productivity Index model to see the productivity level of 11 Zakat Management Organizations in Indonesia, using 2 input variables and 2 output variables. The results showed that all observed Zakat Management Organizations experienced an increase in productivity values during the 2016-2019 period, which means that all OPZs increased their achievements in the field of zakat management. Evidenced by the increase in EFFCH above 1 (1.365), PECH (1.243), and SECH (1.098). on the other hand, technology change or TECH decreased below 1 (0.854). This means that the main sources that influence the increase in OPZ productivity during the 2016-2019 period are the high change in efficiency value (EFFCH) and the stagnation of technological innovation change (TECH).